Towards Coastal Resilience and Sustainability - Heidkamp, C. Patrick; Morrissey, John; Graves, Scott M. (Dynamics of economic space, 2019)
"Coastal zones represent a frontline in the battle for sustainability, as coastal communities face unprecedented economic challenges. Coastal ecosystems are subject to overuse, loss of resilience and increased vulnerability. This book aims to interrogate the multi-scalar complexities in creating a more sustainable coastal zone. Sustainability transitions are geographical processes, which happen in situated, particular places. However, much contemporary discussion of transition is either aspatial or based on implicit assumptions about spatial homogeneity. This book addresses these limitations through an examination of socio-technological transitions with an explicitly spatial focus in the context of the coastal zone. The book begins by focusing on theoretical understandings of transition processes specific to the coastal zone and includes detailed empirical case studies. The second half of the book appraises governance initiatives in coastal zones and their efficacy. The authors conclude with an implicit theme of social and environmental justice in coastal sustainability transitions. Research will be of interest to practitioners, academics and decision-makers active in the sphere of coastal sustainability. The multi-disciplinary nature encourages accessibility for individuals working in the fields of Economic Geography, Regional Development, Public Policy and Planning, Environmental Studies, Social Geography and Sociology" -- Provided by publisher's website.
Keywords: Coastal zone management; Economic aspects; Economic aspects; Sustainable development; dept.egm; faculty_collection

Testate amoebae of peru: Filling the gap in the Neotropics - Bobrov, A.; Mazei, Y.; Buyvolova, A.; Yacher, L. (Revista de Biologia Tropical, 2019)
Testate amoebae diversity from 28 surface (0-3 cm depth) soil samples found near Cuzco (6 samples), in Machu Piсchu (17 samples), in Aguas Calientes (5 samples), and one bottom sediment sample from the Lake Titicaca near Puno were collected during March of 2016 were analyzed. The 144 testate amoebae species and infra-specific taxa belonging to 27 genera were identified. Nineteen amoebae have not been identified to species level and likely represent new taxa. Species richness varied from one to 54 taxa per sample. The highest diversity was found in rainforests followed by those in meadows and agave habitats. The only bottom sample from Lake Titicaca has yielded two hydrobiont species from the genus Difflugia. In the course of the study, several rare species with limited geographical distribution were observed, namely Centropyxis castaneus, C. compressa, C. deflandriana, C. latideflandriana, C. cf. ohridensis, C. cf. ovoides, C. cf. pannosus, C. stenodeflandriana, Cyclopyxis plana, C. profundistoma, Apodera vas, Argynnia retorta, A. spicata, Certesella certesi, Trachelcorythion pulchellum. Our study fills a geographical gap in the distribution of some flagship species with restricted geographic distribution, e.g. Apodera vas and Certesella certesi in Peru. The results illustrate the continuity of expansion species along the Pacific coast. © 2019 by Revista de Biologia Tropical. All rights reserved.
Keywords: Biodiversity; Biogeography; Mountain rainforest; Peru; Protista; dept.egm; peer-reviewed; ⛔ No DOI found

Diel and tidal pCO2 × O2 fluctuations provide physiological refuge to early life stages of a coastal forage fish - Cross, Emma L.; Murray, Christopher S.; Baumann, Hannes (Scientific Reports, 2019)
Coastal ecosystems experience substantial natural fluctuations in pCO2 and dissolved oxygen (DO) conditions on diel, tidal, seasonal and interannual timescales. Rising carbon dioxide emissions and anthropogenic nutrient input are expected to increase these pCO2 and DO cycles in severity and duration of acidification and hypoxia. How coastal marine organisms respond to natural pCO2 × DO variability and future climate change remains largely unknown. Here, we assess the impact of static and cycling pCO2 × DO conditions of various magnitudes and frequencies on early life survival and growth of an important coastal forage fish, Menidia menidia. Static low DO conditions severely decreased embryo survival, larval survival, time to 50% hatch, size at hatch and post-larval growth rates. Static elevated pCO2 did not affect most response traits, however, a synergistic negative effect did occur on embryo survival under hypoxic conditions (3.0 mg L-1). Cycling pCO2 × DO, however, reduced these negative effects of static conditions on all response traits with the magnitude of fluctuations influencing the extent of this reduction. This indicates that fluctuations in pCO2 and DO may benefit coastal organisms by providing periodic physiological refuge from stressful conditions, which could promote species adaptability to climate change.
Keywords: dept.egm

The blue economy: Identifying geographic concepts and sensitivities - Garland, Michaela; Axon, Stephen; Graziano, Marcello; Morrissey, John; Heidkamp, C. Patrick (Geography Compass, 2019)
There is currently no generally accepted definition for the “blue economy,” despite the term becoming common parlance over the past decade. The concept and practice have spawned a rich, and diverse, body of scholarly activity. Yet despite this emerging body of literature, there is ambiguity around what the blue economy is, what it encapsulates, and its practices. Thus far, the existing literature has failed to theorise key geographical concepts such as space, place, scale, and power relations, all of which have the potential to lead to uneven development processes and regional differentiation. Previous research has sought to clarify the ontological separation of land and sea or has conceptualised the blue economy as a complex governmental project that opens up new governable spaces and rationalises particular ways of managing marine and coastal regions. More recently, geographers have called for a critical—and practical—engagement with the blue economy. This paper critically examines the existing literature of the geographies of the blue economy through a structured meta-analysis of published work, specifically its conceptualisations and applications to debates in the field. Results offer the potential to ground a bottom-up definition of the blue economy. In so doing, this paper provides a clearly identifiable rubric of the key geographical concepts that are often overlooked by researchers, policymakers, and practitioners when promoting economic development and technological innovation in coastal and marine environments. © 2019 The Author(s) Geography Compass © 2019 John Wiley & Sons Ltd
Keywords: coastal zone; conceptual framework; dept.egm; economic development; economics; innovation; marine environment; peer-reviewed; power relations; uneven development

Thicker shells compensate extensive dissolution in brachiopods under future ocean acidification - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Environmental Science & Technology, 2019)
Keywords: dept.egm; peer-reviewed

Development of an ecoregional floristic quality assessment method for the northeastern united states - Faberlangendoen, Don; Cameron, Don; Gilman, Arthur V; Metzler, Kenneth J; Ring, Richard M; Sneddon, Lesley (Northeastern Naturalist, 2019)
Floristic quality assessments (FQA) are widely used to assess ecological condition, based on plant species' coefficients of conservatism, or C values, but these values are typically assigned at the state level, limiting their regional consistency. We developed ecoregional C values (eC) using standard expert-based team review, partly informed by preexisting state C values for the 5 EPA ecoregions that cover New England and part of New York. We evaluated a total of 3686 taxa, with separate eC values for each ecoregion in which they occurred. We compared the performance of the C and eC values using the response of FQA metrics (mean C, cover-weighted mean C) to a disturbance gradient, based on readily available datasets in Maine and Vermont. The eC values typically performed moderately better than state values and provide a region-wide tool for assessment methods. All eC values are available on the Universal FQA website. © 2019 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm; peer-reviewed